P80 Aspiration thrombectomy of acute ischemic stroke patients with anterior circulation tandem lesion. (29th August 2022) - Zaidat, OO; Fifi, JT; Hassan, AE
Abstract : Introduction: The study evaluated safety and efficacy of aspiration thrombectomy in acute ischemic stroke (AIS) patients with anterior circulation tandem lesion. Methods: Patients with anterior circulation tandem lesion were extracted from a global, prospective multicenter registry (COMPLETE) that enrolled 650 adults with large vessel occlusion who underwent aspiration thrombectomy with the Penumbra System. Primary efficacy endpoints were post-procedure angiographic revascularization (mTICI score of 2b-3) and 90-day functional outcome (mRS of 0–2). The primary safety endpoint was 90-day all-cause mortality. Revascularization rates were evaluated by core lab and safety data were adjudicated independently. Outcomes of patients with and without stenting were compared. Results: The COMPLETE study enrolled 55 patients with anterior circulation tandem lesions; 20 of those received a stent, and 35 did not. The successful revascularization rate was 89.1%. Good 90-day functional outcome rate was 63.5% (72.2% [95%CI 51.5–92.9%] with stent vs. 58.8% without [95%CI 42.3–75.4%]; P=.34). The 90-day all-cause mortality rate was 7.3% (10.0% [95%Cl 0.0–23.1%] with stent vs. 5.7% without [95%CI 0.0–13.4%]; P =.56). The symptomatic intracranial hemorrhage (ICH) rate at 24 hours was 7.3% (5.0% with stent [95%CI 0.0–14.6%] vs. 8.6% without [95%CI 0.0–17.8%]; P =.62). Conclusions: Aspiration thrombectomy restored blood flow and resulted in good 90-day functional outcome in AIS patients with anterior circulation tandem lesion. The 90-day mortality rate in these patients was low. Clinical outcomes were similar between patients with and without stent. Do you have any conflict of interest to declare? : Yes Conflict of Interest Statement: Zaidat: Grant/research support: Genentech, Medtronic Neurovascular, Stryker; Consultant: Codman, Medtronic Neurovascular, National Institutes of Health (NIH) StrokeNet, Penumbra, Stryker. Other financial or material support: Honoraria: Codman, Medtronic Neurovascular, Penumbra, Stryker. Expert witness. Ownership interest: Galaxy Therapeutics, LLC. Fifi: Grant/research support: Viz.ai. Consultant: Microvention, Stryker, Cerenovus, Penumbra. Other financial or material support: Ownership interest: Imperative Care. DSMB: MIVI, Serenity, Magneto. Hassan: Consultant/Speaker: Medtronic, Microvention, Stryker, Penumbra, Cerenovus, Genentech, GE Healthcare, Scientia, Balt, Viz.ai, Insera therapeutics, Proximie, NeuroVasc, NovaSignal, Vesalio, Rapid Medical, Imperative Care and Galaxy Therapeutics; Principal Investigator: COMPLETE study – Penumbra, LVO SYNCHRONISE – Viz.ai; Steering Committee/Publication committee member: SELECT, DAWN, SELECT 2, EXPEDITE II, EMBOLISE, CLEAR, ENVI, DELPHI; DSMB – COMAND trial.